2022
DOI: 10.1111/jpi.12832
|View full text |Cite
|
Sign up to set email alerts
|

Sini powder with paroxetine ameliorates major depressive disorder by modulating circadian rhythm: A randomized, double‐blind, placebo‐controlled trial

Abstract: Circadian rhythm disorder is a significant risk factor for mental diseases, and the recovery of circadian rhythm function has gradually become a signal of effective antidepressant therapy. Sini powder (SNP) is a classical, traditional Chinese formula for depression treatment. However, few clinical reports have been recorded. This randomized, double-blinded, controlled trial (ChiCTR1900022700) aimed to explore the efficacy of SNP on depression via regulating circadian rhythm. In total, 36 patients with major de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…Chaihu (CH, Radix Bupleuri), Zhishi (ZS, Aurantii Fructus Immaturus), Baishao (BS, Paeoniae Radix Alba), and Gancao (GC, Licorice) are included in SNP [21]. Multiple clinical trials demonstrated that SNP can effectively modulate the circadian rhythms of depression patients [22], demonstrating therapeutic effects on several types of depression, including diabetes with depression [23], functional dyspepsia with depression [24], and post-stroke depression [25]. Animal experiments proved that SNP can regulate the hypothalamicpituitary-adrenal (HPA) axis, and a single pretreatment extract can relieve the increases in serum corticosterone (CORT) and plasma corticotropin-releasing hormone (CRH) levels induced by acute stress, as well as elevating the mRNA expression of the hippocampal glucocorticoid receptor to combat depression [26].…”
Section: Advantages Of Sini Powder Against Depressionmentioning
confidence: 99%
“…Chaihu (CH, Radix Bupleuri), Zhishi (ZS, Aurantii Fructus Immaturus), Baishao (BS, Paeoniae Radix Alba), and Gancao (GC, Licorice) are included in SNP [21]. Multiple clinical trials demonstrated that SNP can effectively modulate the circadian rhythms of depression patients [22], demonstrating therapeutic effects on several types of depression, including diabetes with depression [23], functional dyspepsia with depression [24], and post-stroke depression [25]. Animal experiments proved that SNP can regulate the hypothalamicpituitary-adrenal (HPA) axis, and a single pretreatment extract can relieve the increases in serum corticosterone (CORT) and plasma corticotropin-releasing hormone (CRH) levels induced by acute stress, as well as elevating the mRNA expression of the hippocampal glucocorticoid receptor to combat depression [26].…”
Section: Advantages Of Sini Powder Against Depressionmentioning
confidence: 99%